Crystal structure of trans-bis((E)-7-oxo-4-(phenyldiazenyl)cyclohepta-1,3,5-trien-1-olato)-κ2O,O′)-bis(pyridine-κN)cobalt(II), C36H28CoN6O4 - Hill Tania N.; Koen Renier; Roodt Andreas (Zeitschrift für Kristallographie - New Crystal Structures, 2017)
C36H28Co1N6O4, triclinic, P1̄ (no. 2), a = 6.3166(4) Å, b = 8.5454(5) Å, c = 14.8075(9) Å, α = 105.157(2)°, β = 94.494(3)°, γ = 101.890(2)°, V = 747.5(2) Å3, Z = 1, Rgt(F) = 0.0332, wRref(F2) = 0.0790, T = 100(2) K.